Use of Solar Battery Batteries - Madaliyev Erkin O’rinboyivech; Azamjonov Asadbek Tursunali o’gli (International Journal on Orange Technologies, 2022)
This article aims to increase the efficiency of solar collectors that heat water using solar energy. A new method of tank accumulation of solar water collectors has been proposed and several methods have been demonstrated. The order of water accumulation was studied on the basis of the developed structural elements.